Morphometric analysis of Cryodraco specimens (Notothenioidei: Channichthyidae) from Terra Nova Bay, Ross Sea ... - La Mesa, Mario; Vacchi, Marino (Société Française d'Ichtyologie, 1997)
Biometric and meristic characteristics of ten specimens of Cryodraco caught off Terra Nova Bay, Ross Sea during three Italian Antarctic Expeditions are reported and discussed. The information in literature did not allow an unambiguous taxonomic diagnosis of the studied specimens showing some but not all the distinctive characters of Cryodraco atkinsoni. For the taxonomic diagnosis of the genus Cryodraco it is suggested to select those morphological characters which show minor changes with the ontogenesis. ...